Effects of climatic change on the phenology of butterflies in the northwest Mediterranean Basin - Constantí Stefanescu; Josep Peñuelas; Iolanda Filella (Global Change Biology, 2003)
Phenological changes in response to climatic warming have been detected across a wide range of organisms. Butterflies stand out as one of the most popular groups of indicators of climatic change, given that, firstly, they are poikilothermic and, secondly, have been the subject of thorough monitoring programmes in several countries for a number of decades. Here we provide for the first time strong evidence of phenological change as a consequence of recent climatic warming in butterflies at a Spanish site in the northwest Mediterranean Basin. By means of the widely used Butterfly Monitoring Scheme methodology, three different phenological parameters were analysed for the most common species to test for trends over time and relationships with temperature and precipitation. Between 1988 and 2002, there was a tendency for earlier first appearance dates in all 17 butterfly species tested, and significant advances in mean flight dates in 8 out of 19 species. On the other hand, the shape of the curve of adult emergence did not show any regular pattern. These changes paralleled an increase of 1–1.5°C in mean February, March and June temperatures. Likewise, a correlation analysis indicated the strong negative effect of spring temperature on phenological parameters (i.e. higher temperatures tended to produce phenological advances), and the opposite effect of precipitation in certain months. In addition, there was some evidence to indicate that phenological responses may differ between taxonomic lineages or species with similar diets. We discuss the consequences that these changes may have on species' population abundances, especially given the expected increase in aridity in the Mediterranean Basin caused by current climatic warming. We predict that varying degrees of phenological flexibility may account for differences in species' responses and, for multivoltine species, predict strong selection favouring local seasonal adaptations such as diapause phenomena or migratory behaviour.

Partitioning of water and nitrogen in co-occurring Mediterranean woody shrub species of different evolutionary history - Iolanda Filella; Josep Peuelas (Oecologia, 2003)